Pengaruh Service Marketing Mix dan Customer Value Terhadap Kepuasan Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Maritim Raja Ali Haji - Iranita Iranita (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
The object of the study was obtained about the effect of Service Marketing Mix and Customer Value on student satisfaction in the UMRAH Faculty of Economics management study program. The type of research is explanatory. The results of the study indicate that the service marketing mix consists of products (product), price (price), distribution (place), promotion (people), people (people), direct evidence (physical evidence) and process (process, and customer value includes Customer benefit and customer cost both partially and simultaneously has a strong influence on student satisfaction in the UMRAH Faculty of Economics Management Study Program